Experimental Investigation of the Pressure of Crystallization of Ca(OH)2: Implications for the Reactive Cracking Process - S. Lambart; H. M. Savage; B. G. Robinson; P. B. Kelemen (Geochemistry, Geophysics, Geosystems)
Abstract Mineral hydration and carbonation can produce large solid volume increases, deviatoric stress, and fracture, which in turn can maintain or enhance permeability and reactive surface area. Despite the potential importance of this process, our basic physical understanding of the conditions under which a given reaction will drive fracture (if at all) is relatively limited. Our hydration experiments on CaO under uniaxial loads of 0.1 to 27 MPa show that strain and strain rate are proportional to the square root of time and exhibit negative, power law dependence on uniaxial load, suggesting that (1) fluid transport via capillary flow is rate limiting and (2) decreasing strain rate with increasing confining pressure might be a limiting factor in reaction driven cracking at depth. However, our experiments also demonstrate that crystallization pressure due to hydration exceeds 27 MPa (consistent with a maximum crystallization pressure of 153 MPa for the same reaction, Wolterbeek et al., https://doi.org/10.1007/s11440‐017‐0533‐5). As a result, full hydration can be achieved at crustal depths exceeding 1 km, which is relevant for engineered fracture systems.